The Effect of Working Conditions and Leadership Style on the Performance of Babinsa Koramil 07 Makassar City - Alfirah Kidang; Muhammad Najib Kasim; Abdul Muttalib (IECON: International Economics and Business Conference, 2024)
This study aims to determine the effect of working conditions and leadership style on the performance of Babinsa (Village Supervisory Non-Commissioned Officers) of Koramil 07 Makassar City. The research employs a quantitative descriptive approach, analyzing the responses obtained from a questionnaire completed by 60 Babinsa of Koramil 07 Makassar City. The data analysis techniques utilized include descriptive data analysis, multiple linear regression analysis, classical assumption tests, and hypothesis testing. The results of the study demonstrate that the working conditions variable has a significant positive effect on Babinsa performance, indicating that better working conditions lead to improved performance. On the other hand, leadership style does not have a significant effect on Babinsa performance, suggesting that leadership style alone may not be a primary driver of performance in this context. However, when considered together, working conditions and leadership style jointly influence the performance of Babinsa in Koramil 07 Makassar City. These findings suggest that while leadership style may not be a direct factor in performance, optimizing working conditions can have a more significant impact. Therefore, efforts to improve working conditions should be prioritized to enhance Babinsa performance, and further research could explore additional factors contributing to their performance.